Histomorphometrical and Histopathological Assessment of in Ovo Methionine Injection on the Skin Layers and Its Collagen Bundles of Chicken Embryo - Mohammad Naser Nazem; Hadi Tavakoli; Sayed Mohsen Sajjadian (Negah Institute for Scientific Communication, 2015)
Introduction: Skin resistance is greatly dependent on its collagen amount and nutritional substances such as crude protein that affect the skin collagen can indirectly influence the skin resistance and increase its strength. In this regard, this study aimed to evaluate the effect of in ovo methionine injection on histomorphometry of the skin layers. Methods: Thirty fertilized eggs of Ross 308 broiler chicks were randomly divided into 3 equal groups of 10 eggs each. On day 4 of incubation, the first and the second group (treatment groups) were injected by 40 mg and 50 mg of methionine (Met) dissolved in 0.5 mL of phosphate buffered saline into the yolk sac, respectively. The third (control) group was only received 0.5 mL of phosphate buffered saline. On the day 18 of incubation, the eggs were removed from the incubator and the embryos were killed humanely. Then, the samples were taken from the skin of thoracic region of each embryo for histomorphometric study under the light microscope. Results: The results indicated no significant increase in the epidermal thickness in Met (treatment) groups except for Met 40 compared to controls and Met 50 (P<0.05). Dermal thickness in the Met groups showed significant increase in Met 50 group compared to the other groups (P<0.05). Collagen bundles thickness of both dermis layers decreased in Met groups. Conclusion: Obtained results revealed that methionine may stimulate immature collagen synthesis.